Inflammatory signalling as mediator of epigenetic modulation in tissue-specific chronic inflammation. - Bäckdahl, L; Bushell, A; Beck, S (2009)
Recent successes of therapeutic intervention in chronic inflammatory diseases using epigenetic modifiers such as histone deacetylase inhibitors and inhibitors of DNA methylation suggest that epigenetic reprogramming plays a role in the aetiology of these diseases. The epigenetic signature of a given immune cell is reflected in the history of modifications from different signals the cell has been subjected to during differentiation. Like other cells, differentiating immune cells are dependent on a complex combination of inter- and intracell signalling as well as transcription machineries to modulate their epigenomes in order to mediate differentiation. Despite extensive research into these processes, the link between cellular signalling and epigenetic modulation remains poorly understood. Here, we review recent progress and discuss key factors driving epigenetic modulation in chronic inflammation.